Penerapan pendekatan saintifik untuk meningkatkan kemampuan komunikasi matematis siswa SMP kelas VII - Hani, Enur; Hutajulu, Masta; Pertiwi, Citra Megiana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study intends to determine the improvement of mathematical communication skills of grade VII students using a scientific approach. This study uses a quasi-experimental method. The population of this study is grade VII students, while the sample of this study is class VII-A as a control class and class VII-C as an experimental class in one of the junior high schools in Cimahi City. The research instrument used for the KKomM description test was four questions. The collected data was processed with descriptive statistics and IBM SPSS Statistics-25-assisted inferential statistics. This study shows that KKomM students who use a scientific approach are better than students who use ordinary learning.